2019
DOI: 10.1590/s0102-053620190112
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic stability of strawberry cultivars based on physicochemical traits of fruits

Abstract: Strawberry shows genetic variability between cultivars and, environmental elements affect the physicochemical traits of fruits when assessed under different environments. So, assessment of the stability of physicochemical traits is a tool that assists the producer in the choice of the cultivar with higher acceptance in the consumer market. This study aimed to assess the stability of strawberry cultivars based on physicochemical traits of fruits on three environments using the additive main effects with multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…These strengths are mainly related to the Albion cultivar and the Imported origin of transplants. Our results corroborate with Gabriel et al (2019), which studying 13 strawberry cultivars observed that Albion presents high values for fresh rmness and • Brix.…”
Section: Strengths and Weaknesses Of Treatmentssupporting
confidence: 91%
“…These strengths are mainly related to the Albion cultivar and the Imported origin of transplants. Our results corroborate with Gabriel et al (2019), which studying 13 strawberry cultivars observed that Albion presents high values for fresh rmness and • Brix.…”
Section: Strengths and Weaknesses Of Treatmentssupporting
confidence: 91%
“…The cultivar Camarosa is known for its high yield and large, firm, and tasty fruits [44]. Therefore, the superiority of hybrids regarding yield traits when 'Camarosa' was one of the parents is due to the presence of a high number of favorable alleles in this cultivar, which makes it a promising parent for strawberry breeding programs [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The cultivar Camarosa is known for its high yield and large, firm, and tasty fruits [44]. Therefore, the superiority of hybrids regarding yield traits when 'Camarosa' was one of the parents is due to the presence of a high number of favorable alleles in this cultivar, which makes it a promising parent for strawberry breeding programs [44,45]. Currently, 'Camarosa' has been the most planted cultivar in the world, being a market leader for over twenty years [46,47], but it has sensitivity to photoperiod (short-day) and susceptibility to main diseases [45,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cultivars with high TSS values are well accepted by consumers for fresh consumption. Variation observed between genotypes can be attributed to some factors, such as characteristics of the cultivar, influence of the place of cultivation and temperature(Ali et al, 2011;Hirsch et al, 2012;Guedes et al, 2013;Gabriel et al, 2019). The pH and other characteristics found in fruit can be used as indicators to define the best genotypes for the fresh market or industry.…”
mentioning
confidence: 99%